The Reform of European Public Debt Regulations – an Opportunity and a Challenge for EU Member States - Postuła, Marta; Kawarska, Anna; Chmielewski, Wojciech (Comparative Economic Research. Central and Eastern Europe, 2025)
The article examines how the European Commission’s proposal to reform the Stability and Growth Pact (SGP) in terms of the pace of public debt reduction may affect basic economic parameters, such as GDP, consumption and investment levels, as well as fiscal parameters like the scale of subsidies and taxation levels of production and goods. This analysis focuses on two groups of EU countries: those with public debt below 60% of GDP (Group 1) and those with public debt above 60% of GDP (Group 2). In the first stage of the study, using Eurostat data from 1995–2022 and employing a fixed effects model, we show that in Group 1, the impact of public debt on economic growth is statistically significant (unlike in Group 2). In the second stage, we conduct a detailed analysis of the impact of public debt on basic macroeconomic parameters (GDP growth components) and fiscal policy in countries with high levels of public debt. We simulate both moderate and drastic variants for reducing public debt relative to GDP. The results show that in these countries, debt reduction leads to a decrease in consumer spending, an increase in investments, and an increase in taxes on production and imports. Based on these results, we recommend that the SGP reform should prioritize a gradual reduction of the public debt-to-GDP ratio because implementing drastic solutions would require deep cuts in public spending and tax increases in a short timeframe. We also highlight the need to consider exceptional situations in which the SGP rules may be suspended, as was the case with the COVID-19 pandemic.